Cotton Seedling Diseases and Management Strategies - Djurayevna, Gulmurodova Shaxnoza (American Journal of Biology and Natural Sciences, 2026)
Cotton (Gossypium hirsutum L.) is a vital industrial crop, yet its early growth stages are highly vulnerable to the seedling disease complex. This complex, primarily driven by soilborne fungal pathogens such as Rhizoctonia solani, Pythium spp., and Fusarium spp., leads to significant stand loss through pre- and post-emergence damping-off and soreshin. These diseases are particularly devastating in cool, moist soil conditions, which favor fungal activity over seedling development. This article examines the symptomatic characteristics of major seedling diseases and evaluates various management strategies. Effective control requires an Integrated Disease Management (IPM) approach, combining cultural practices-such as optimal planting timing and crop rotation-with chemical interventions like systemic seed treatments and in-furrow fungicides. Furthermore, the role of biological control agents is discussed as a sustainable alternative. By implementing these combined strategies, growers can ensure uniform plant stands and protect the yield potential of the cotton crop from the very beginning of the growing season.